Exploring Computational and Biophysical Tools to Study the Presence of G-Quadruplex Structures: A Promising Therapeutic Solution for Drug-Resistant Vibrio cholerae - Shankar, Uma; Jain, Neha; Majee, Prativa; Kodgire, Prashant; Sharma, Tarun Kumar; Kumar, Amit (Frontiers in Genetics, 2020)
Vibrio cholera, a gram-negative bacterium that causes cholera has already caused seven major pandemics across the world and infects 1.3 to 4 million people every year. The cholera treatment primarily involves oral rehydration therapy supplemented with antibiotics. But recently, multidrug-resistant strains of V. cholerae has emerged. High genomic plasticity further enhances the pathogenesis of this human pathogen. Guanines in DNA or RNA assemble to form G-quadruplex structures which have emanated to be potential drug targeting sites for different pathogenic bacteria and viruses. In this perspective, we carried out genome-wide hunt in the V. cholerae using bio-informatics approach and observed 85 G-quadruplex forming motifs (VC-PGQs) in chromosome I and 45 PGQs in chromosome II. Ten putative G-quadruplex forming motifs (VC-PGQs) were selected on the basis of conservation throughout the genus and functional analysis displayed their location in the essential genes of the bacteria coding for example methyl-accepting chemotaxis protein, orotate phosphoribosyl transferase protein, amidase proteins, etc. The predicted VC-PGQs were validated using different bio-physical techniques including Nuclear Magnetic Resonance spectroscopy, Circular Dichroism spectroscopy, and electrophoretic mobility shift assay which evidently demonstrated the formation of highly stable G-quadruplex structures in the bacteria. The interaction of these VC-PGQs with the known specific G-quadruplex ligand, TMPyP4 was analyzed using ITC and molecular dynamics studies that displayed the stabilization of the VC-PGQs by the G-quadruplex ligands and thus represents a potential therapeutic strategy against this enteric pathogen by inhibiting the PGQ harboring gene expression thereby inhibiting the bacterial growth and virulence. In summary, this study reveals the presence of conserved G-quadruplex forming motifs in the V. cholerae genome that can be postulated to be a plausible attempt to treat the multi-drug resistance problem of the notorious enteric pathogen.